Activation of hepatic stellate cell in Pten null liver injury model. Issue 1 (December 2016) - He, Lina; Gubbins, James; Peng, Zhechu; Medina, Vivian; Fei, Fan; Asahina, Kinji; Wang, Jiaohong; Kahn, Michael; Rountree, Carl; Stiles, Bangyan
Abstract Background Hepatic fibrosis is a prominent pathological feature associated with chronic liver disease including non-alcoholic hepatosteatosis (NASH), and a precursor for liver cancer development. We previously reported that PTEN loss in the liver, which leads to hyperactivated liver insulin signaling results in NASH development. Here we used the same mouse model to study the progression from steatosis to fibrosis. Results ThePten null livers develop progressive liver fibrosis as indicated by Sirius Red staining and increased expression of collagen I, Timp 1, SMAα, and p75NTR. Consistently, hepatic stellate cells (HSCs) isolated fromPten null livers are readily activated when compared with that from mice with intact PTEN. Deletion of AKT2, the downstream target of PTEN signal, blocked NASH development, and alleviated fibrosis. HSCs from thePten/Akt2 double null mice are quiescent like those isolated from the control livers. Our analysis shows that the activation of HSCs does not depend on the intrinsic signals regulated by PI3K/AKT, the target of PTEN, but does depend on steatosis and injury to the liver. During the progression of liver fibrosis in thePten null model, Wnt ligands and signaling receptor are induced, concurrent with the reduction of sFRP5, a Wnt antagonist. We showed that treatment of HSCs with Wnt receptor antagonist blocks the observed morphological changes when HSCs undergo activation in culture. This signal appears to be mediated by β-catenin, as manipulating β-catenin signaling alters marker gene expressions of HSC activation. Conclusions Wnt/β-catenin activation serves as an important mediator for fibrosis development resulting from NASH using a mouse model where NASH is mimicked by PTEN loss.